(untitled) (TEST XY. Critical review of studies on the representation of architecture and use of the image in science and art, 2017)
«Negligent speech doth not only discredit the person of the Speaker, but it discrediteth the opinion of his reason and judgment; it discrediteth the force and uniformity of the matter, and substance». The visual representation is one of the more direct and effective ways to communicate. Crossing the boundaries between image and language, Johnson’s aphorism manifests a clear ambivalence: a negligent representation undermines not only the reasons of those who produce it, but the substance itself of his communication. Working on image it means to operate design choices, knowing how to interpret, encode and translate the thinking into a visual form. In communica- tion design, as in art, the image then takes on a central role. Its structure is based on complex and elaborate mechanisms often in dyadic and symbiotic relationship with the verbal language. Precisely the nature of this structure has been and continues to be studied in order to identify and describe the mechanisms that regulate its effectiveness. However, the theoretical framework in which often the visual image is brought back is to the psychology of perception. This paper intends instead to focus on mathematical constructs that govern the definition of an image, with particular emphasis on graphic design. In this context the visualization appears the foundational tool to bridge the limitations of the logos, and the contribution of a mathematical order under- lying the figuration defines non-arbitrary ways of a successful transmission of the information. Through the analytical study of mathematical artifacts it is proposed a new interpretation of a vast repertoire of illustrations in which, sometimes unexpectedly, the science of numbers or geometry make the graphic message successful. The study carried out does not run through an unexplored territory, but it is part of a research frontier prolific of significant outcomes.